First approach to the consumption of fauna and herd management in the south of Pozuelos (Puna de Jujuy, Argentina) in late pre-Hispanic and colonial times (13th to 18th centuries) - Torres Vega, Lucrecia Marina Raquel (2021)
The comparative analysis of different zooarchaeological assemblages recovered in sites in the south of the Pozuelos basin (puna de Jujuy, Argentina) dated between the 13th and 18th centuries, allowed us to recognize some aspects of fauna consumption and herd managment practices of the ancient local inhabitants. We will consider the transformations and persistence through time, contemplating the functional variations and contextual aspects of the analyzed occupations. Camelids are the most represented species in all groups, making the consumption of pastoral resources visible throughout the sequence. For the occupations of the thirteenth and fourteenth centuries we have recorded wild camelids, the presence of other taxa in the samples being very scarce, in the colonial occupations the absence of European fauna in the excavated contexts is striking. The age classes suggest that mixed resource exploitation strategies were practiced, at least during the 13th and 14th centuries. Finally, the similarities and differences found between the sets seem to be due to the particularities acquired by the domestic occupations.